Analysis of the Implementation of Quality Assurance in Equivalency Education Based on the 8 National Education Standards at PKBM Dahlia, Pekanbaru - Delva Syara; Rahmat Fahmi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Equivalency education serves as an alternative educational service for communities with limited access to formal education. PKBM Dahlia Pekanbaru provides Package A Package B Package C programs as part of nonformal education services. Literature review indicates equivalency education contributes to improving human resource quality through flexible learning systems based on community needs. This study applies a literature review method using data from official documents and relevant scientific articles. The findings show the implementation of National Education Standards in graduate competency learning process facilities assessment systems. Learning activities run flexibly based on learner characteristics. Assessment systems describe student learning outcomes. Learning facilities support educational activities. The conclusion indicates quality assurance implementation operates adequately with the need for improvement in learning facilities and institutional management.